(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Embedding is one of the phenomena that has a functional effect in the Holy Qur’an, and In the field of interpretation in particular, grammarians have tried to set strict limits for this phenomenon. Rhetoric and prosody are two of the many sciences that incorporate embedding. Ibn Rašīq, also known as al-Kairwānī, gave the following definition of embedding: (embedding occurs when the rhyme or a word before it is related to what comes after it... the more away the word related to the second verse is from the rhyme, the easier it is to question the embedding). This is also true of the most well known rhetoricians. Both the Basran and the Kufic have influenced grammarians’ conceptions of embedding. As a means of correcting the attachment of an accusative verb or semi-verb by estimating an appropriate factor in meaning and action and adding its meaning to the previously mentioned factor, the Basrians adopted the inferential method to limit the concept of embedding, allowing it in the verb rather than the letter. Here, the attachement includes the accusative cases from the objects. They considered that the verb includes the meaning of another verb, leading to one word indicating two different meanings simultaneously. As for Kufic embedding, it includes correcting the attachment of a letter or an adverb related to the factor in terms of meaning. They allowed the letter to be replaced by another letter; The hadith scholars followed the grammarians of Basra in their approach, and established standard rules and regulations for embedding, including: First: The embedding must adhere to Arab taste. Second: There is an appropriateness between the two actions. Third: Linguistic evidence supporting the observation of the other action. The First Requirement: Embedding in the opinion of the predecessors and the hadith scholars The opinions of the grammarians and the Arabists have multiplied about the significance of embedding between the letter and the verb: (In their saying, they elevated "perhaps" to the stature of "was." : - Perhaps the gyros is miserable), as we notice that Sibawayh used it as a tool in the interpretation of grammatical problems; It seems to the researcher in that more than the significance of the word on one meaning, and the ideology of Ibn Jinni (393 - 1002) appears in his saying: (Know that if the verb is in the sense of another verb and one of them exceeds a letter and the other in another letter, then the Arabs may expand, so one of the two letters will be placed in the location of the other to mark that this verb is in the meaning of that other verb). It seems that Ibn Jinni has overcome the ruling and limited it to the transitive verb with the letter; Al -Zamakhshari (538 - 1143) pursued Ibn Jinni, and he believes that the embedding is giving the sum of two meanings is stronger than giving a meaning, and we notice that Al -Zamakhshari restricted the embedding in the verb. As for Al-Ashmouni (929-1464), he says: (It is imbuing a word with the meaning of another word and giving it its meaning so that the word becomes the function of two words.). If we review the opinions of the hadith scholars, we notice that there is an educational tendency to restrict this phenomenon, and the Linguistic Academy in Cairo welcomed this phenomenon and established elements for it - which we mentioned previously -, so the Scientific Academy holds embedding is when a verb or something in its meaning is performed, and it gives its form on transgression.